The First Evidence of Gibberellic Acid’s Ability to Modulate Target Species’ Sensitivity to Honeysuckle (Lonicera maackii) Allelochemicals - Csengele Éva Barta; Brian Colby Jenkins; Devon Shay Lindstrom; Alyka Kay Zahnd; Gyöngyi Székely (Plants, 2023)
Invasive species employ competitive strategies such as releasing allelopathic chemicals into the environment that negatively impact native species. Decomposing Amur honeysuckle (Lonicera maackii) leaves leach various allelopathic phenolics into the soil, decreasing the vigor of several native species. Notable differences in the net negative impacts of L. maackii metabolites on target species were argued to depend on soil properties, the microbiome, the proximity to the allelochemical source, the allelochemical concentration, or environmental conditions. This study is the first to address the role of target species’ metabolic properties in determining their net sensitivity to allelopathic inhibition by L. maackii. Gibberellic acid (GA3) is a critical regulator of seed germination and early development. We hypothesized that GA3 levels might affect the target sensitivity to allelopathic inhibitors and evaluated differences in the response of a standard (control, Rbr), a GA3-overproducing (ein), and a GA3-deficient (ros) Brassica rapa variety to L. maackii allelochemicals. Our results demonstrate that high GA3 concentrations substantially alleviate the inhibitory effects of L. maackii allelochemicals. A better understanding of the importance of target species’ metabolic properties in their responses to allelochemicals will contribute to developing novel invasive species control and biodiversity conservation protocols and may contribute to applications in agriculture.